Logic, language, information, and computation : 24th International Workshop, WoLLIC 2017, London, UK, July 18-21, 2017, Proceedings /: 24th International Workshop, WoLLIC 2017, London, UK, July 18-21, 2017, Proceedings. (2017) - Unknown
No abstract available